The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.2147/idr.s4796
|View full text |Cite
|
Sign up to set email alerts
|

Anidulafungin and its role in candida infections

Abstract: Candida infections continue to play a significant role not only in critically ill and immunocompromised patients but also in non-compromised patients. The incidence of systemic fungal infections in the United States has been on the rise for the past 30 years. Anidulafungin and all echinocandins inhibit glucan synthase thus inhibiting the formation of 1,3-β-D-glucan which is an essential component of the fungal cell wall. The decrease in 1,3-β-D-glucan results in the osmotic lysis of the cell, resulting in fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…[1][2][3] This relatively new class of antifungals is characterized by a low probability of drugdrug interactions. 4 Echinocandins are usually well tolerated, nevertheless rare adverse events can occur.…”
Section: What Is Known and Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] This relatively new class of antifungals is characterized by a low probability of drugdrug interactions. 4 Echinocandins are usually well tolerated, nevertheless rare adverse events can occur.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…With rising incidence of fungal infections, echinocandins have become important in the treatment of invasive Candidiasis and are recommended for initial targeted therapy. [1][2][3] This relatively new class of antifungals is characterized by a low probability of drugdrug interactions. 4 Echinocandins are usually well tolerated, nevertheless rare adverse events can occur.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Candida UTI and candidemia are also frequent in ICU patients with high rate of mortality and morbidity [ 1 , 5 ]. Candidemia is accountable for 5.6 to 10% of nosocomial bloodstream infections [ 55 , 56 , 57 ], and studies found that anidulafungin exhibits superior clinical outcomes than fluconazole in the treatment of bloodstream infections caused by Candida strains susceptible or resistant to fluconazole [ 33 , 58 , 59 ]. In this study, Candida pneumonia was relatively higher than Candida UTI and candidemia in both groups, and patients of NEAT group demonstrated higher rate of CP (22.2%) than the patients of EAT group (3.8%).…”
Section: Discussionmentioning
confidence: 99%
“…For a confirmatory diagnosis of an invasive fungal infection without distinguishable signs and symptoms in the critically ill patients during the early hours of ICU admission is still a complicated issue for the clinicians worldwide [ 22 ]. Initiation of IC treatment based on microbial culture report is a time consumable basis of treatment, and in some cases, clinical conditions of patients are extremely deteriorated before getting the culture report in hand [ 58 ]. Study found that approximately 40%-50% of patients are admitted in ICU with candidemia and its diagnosis takes days to confirm [ 2 , 61 ].…”
Section: Discussionmentioning
confidence: 99%